THE EXIXTENCE OF DAAI TV INDONESIA IN THE NEW MEDIA ERA - Novalia Agung Wardjito Ardhoyo (Universitas prof. Dr. Moestopo (Beragama), 2022)
Mostly television station operates by advertiser support. But not with DAAI TV. There are no product advertisements like most television stations in Indonesia. However, DAAI TV has been broadcasting since 2007 and still exists until now without advertiser support. This research hopes to be useful in increasing the reader's insight, how DAAI TV's business model is and whether there are economic or political elements behind its operations. This research uses a qualitative approach with a case study method. The data needed in this analysis was obtained through interviews with several parties from DAAI TV and documentation studies. The research procedure was carried out within the framework of descriptive analysis. It can be concluded that the television station DAAI TV is a media that uses a different concept from other media, namely social networks. And with its uniqueness as a television that spreads love, DAAI TV hopes that through its shows, it will have a special place in the hearts of viewers.